Three new species of wood-boring bivalves (Mollusca: Xylophagaidae) from the deep Northwest Atlantic Ocean - Voight, Janet R. (Zootaxa, 2024)
Ruth Turner’s studies of xylophagaids, wood-boring bivalves, documented the very existence of wood-borers in the deep sea and made the northwestern Atlantic fauna among the best known. However, her work focused on specimens from less than 2000 m depth. Here study of specimens from depths over 2000 m deposited in the Smithsonian collections extends our knowledge of this fauna. Despite the lack of molecular data, three species, Xylophaga microdactylus n. sp., Xylophaga platyplax n. sp. and Xylophaga lambula n. sp. are described; only X. lambula n. sp. pertains to Xylophaga s.s. Turton. Additional records of the known species, Xyloredo nooi Turner, Xylonora atlantica (Richards), Abditoconus cf. anselli (Harvey), Xylophaga clenchi Turner & Culliney, Feaya dostwous (Voight), and Xylopholas cf. altenai Turner are provided, with some supplemental information on morphological characters. The presence of Xylophaga microdactylus n. sp., which is remarkably similar to X. microchira Voight, suggests a close relationship between the xylophagaids of the deep northwestern Atlantic and northeastern Pacific. The depth distributions of northwest Atlantic species are detailed with supplemental data from the literature to explore potential patterns of distribution.